2013
DOI: 10.1007/s11205-013-0512-7
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attachment, Love Styles, Relationship Experiences and Subjective Well-Being: Cross-Cultural and Gender Comparison between Americans, Portuguese, and Mozambicans

Abstract: Attachment security, love styles, and romantic relationship experiences are closely associated with subjective well-being (SWB). A few studies have empirically observed significant relations between these variables. However, no studies have included all of these predictors to analyze the unique contribution of each to SWB, and no crosscultural studies have analyzed these variables simultaneously. This article examined (a) the relations between attachment security, love styles, romantic relationship experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 51 publications
6
29
0
5
Order By: Relevance
“…A few cross-cultural studies have been conducted, and these studies have found more similarities than differences between Portuguese individuals and individuals from other countries (mainly the United States and Europe) in the distribution of attachment styles. However, these previous studies have exclusively focused on adult romantic attachment assessed by the ECR (Galinha, Oishi, Pereira, Wirtz, & Esteves, 2013;Moreira et al, 1998;Schmitt et al, 2004). The ECR-RS will allow for the expansion of the research questions and focus by assessing different relational domains.…”
Section: The Need For a Portuguese Versionmentioning
confidence: 99%
“…A few cross-cultural studies have been conducted, and these studies have found more similarities than differences between Portuguese individuals and individuals from other countries (mainly the United States and Europe) in the distribution of attachment styles. However, these previous studies have exclusively focused on adult romantic attachment assessed by the ECR (Galinha, Oishi, Pereira, Wirtz, & Esteves, 2013;Moreira et al, 1998;Schmitt et al, 2004). The ECR-RS will allow for the expansion of the research questions and focus by assessing different relational domains.…”
Section: The Need For a Portuguese Versionmentioning
confidence: 99%
“…Several studies have explored associations between attachment insecurities and aspects of life satisfaction (Galinha, Oishi, Pereira, Wirtz, & Esteves, 2013;Karreman & Vingerhoets, 2012;Lavy & Littman-Ovadia, 2011;Li & Fung, 2014;Sadava, Busseri, Molnar, Perrier, & DeCourville, 2009). In general, the results show that both forms of insecure attachment (attachment anxiety and avoidance) are inversely related to life satisfaction.…”
Section: Adult Attachment Insecurities and Life Satisfactionmentioning
confidence: 99%
“…Bezüglich der Partnerschaftszufriedenheit konnten wir die Ergebnisse früherer Studien replizieren (Fricker/Moore 2002;Galinha et al 2013;Gana et al 2013;Hendrick et al 1988 (Bierhoff et al 1993;Fricker/Moore 2002;Hendrick et al 1988;Morrow et al 1995) (Bierhoff et al 1993) ausfüllen zu lassen. Eine Erklärung der verschiedenen Komponenten der Liebe kann ein wichtiger Schritt sein, um Paaren zu helfen, ihre Probleme zu bewältigen oder auch zu lösen (Moss/Schwebel 1993) sowie positive Beschreibungen für ihre Unterschiede und Gemeinsamkeiten zu finden (Hendrick 2004).…”
Section: Zusammenfassung Und Diskussionunclassified
“…Studien dazu fanden lediglich signifikante Zusammenhänge beim romantischen, altruistischen sowie spielerischen Liebesstil. Eros hängt durchgehend positiv mit Partnerschaftszufriedenheit zusammen (Fricker/Moore 2002;Galinha et al 2013), während in weiteren Studien zusätzlich ein positiver Zusammenhang zwischen Agape und Partnerschaftszufriedenheit gefunden wurde (Bierhoff et al 1993;Hendrick et al 1988;Morrow et al 1995;Lin/Huddleston-Casas 2005;Gana at al. 2013 [jedoch nur bei den Männern]).…”
Section: Introductionunclassified